Photo-induced Aggregation of Single-walled Carbon Nanotubes from Dispersion by Using a Photochromic Dispersant - Seki, Yuki; Matsunaga, Kazuki; Ke, Yuting; Takebayashi, Toma; Ninoyu, Masaya; Kakugawa, Keiju; Lee, Vannajan Sanghiran; Takahara, Shigeru (The Society of Photopolymer Science and Technology, 2019)
Dipropylheterocoerdianthrone (DPHCD) was found to be a potential photo-reactive dispersant of single-walled carbon nanotubes (SWNTs). DPHCD was able to well disperse SWNTs in chloroform. DPHCD is easily photo-oxidized by the irradiation of visible light to form the endoperoxide with a bent structure under oxygen or air atmosphere. Then, SWNTs were photo-precipitated from the DPHCD/SWNTs dispersion. The precipitation was able to disperse again after the photochromic reaction to turn back DPHCD from the endoperoxide and sonication. Such photo-induced precipitation was also observed in DPHCD/SWNTs complex film. The SWNTs precipitates were analyzed by FT-IR and Raman spectra measurements, and discussed about selectivity of DPHCD on chirality, and elimination of the dispersant. © 2019 SPST.